Then, Defense Against the Sea...Now, Defense Against Disease - Hercules Incorporated (1947 Hercules Advertisements, 1947)
Advertisement for Thanite, the brand name for a synthetic toxicant manufactured and sold by the Hercules Powder Company for use in insecticides. The advertisement details the varied uses of naval stores past and present, highlighting Hercules' discovery and development of new products and uses. This advertisement appeared in the February 1947 issue of Naval Stores Review. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) initially specialized in the manufacture of explosives and smokeless powders and subsequently diversified its business to encompass a variety of industrial products, including pine and paper chemicals, synthetics, pigments, polymers, and cellulose.
Keywords: Chemical industry; Research, Industrial; Hercules Incorporated; Corporations; Naval stores; Insecticides; Advertising, Industrial; Women in advertising